Serum cortisol as a moderator of the relationship between serum testosterone and Olympic weightlifting performance in real and simulated competitions - Crewther, B. T.; Obminski, Z.; Cook, C. J. (Biology of Sport, 2018)
Some equivocality exists regarding the effect of testosterone (T) on competitive performance with cortisol (C) implicated as a moderating factor. This study investigated whether C is moderating the T relationship with Olympic weightlifting (OWL) performance during real and simulated competitions. We monitored 105 male athletes (age 19.3±3.7 years); 46 during real OWL competitions (e.g., national age championships) and 59 across simulated events (e.g., talent identification). Serum T and C were assessed before warming up and within 15 minutes of event completion. Performance was indexed by the total combined load across the snatch and clean and jerk exercises. Hierarchical linear regression and simple slopes were employed to test the hormone and performance relationships. Pre-competition T (pre-T) and C (pre-C) were unrelated to OWL performance when controlling for competition type, time of day, age, and body mass (model=75.6% variance). However, the pre-T × pre-C interaction was significant (model=77% variance). Upon exploring this interaction, different pre-T and performance relationships emerged for males with high pre-C (ß=-9.96) and low pre-C levels (ß=9.04), with diverging slopes (p=0.006). The assessment of T changes and pre-C produced similar results. The association between male T and performance during OWL competition was determined by C activity, which could explain conflicting reports of T as a correlate of competitive abilities. Our results imply that T and C are not strictly anabolic and catabolic biomarkers of performance, respectively, but rather they exert complementary actions that could depend on task, situational and environmental needs.